Nonparametric Hybrid Phillips Curves Based on Subjective Expectations: Estimates for the Euro Area - Marco Buchmann (European Central Bank (ECB), 2009)
This paper addresses the estimation of Phillips curve equations for the euro area while employing less stringent assumptions on the functional correspondence between price inflation, inflation expectations and marginal costs. Expectations are not assumed to be an unbiased predictor of actual inflation and instead derived from the European Commission's Consumer Survey data. The results suggest that expectations drive inflation with a lag of about 6 months, which casts further doubt on the validity of the New Keynesian Phillips curve. Moreover, the trade off between inflation and real economic activity is not vertical in the short run. Non- and Semiparametric estimates reveal an important nonlinearity in the sense that demand pressure on price inflation is not invariant to the state of the economy as it increases considerably at times of high economic activity. Conventional linear Phillips curves cannot capture this empirical regularity. Some implications for monetary policy are discussed.
Keywords: C14; E31; E32; 330; inflation; monetary policy; Non- and Semiparametric Econometrics; Phillips curve; survey expectations; Inflationserwartung; Phillips-Kurve; Nichtparametrisches Verfahren; Eurozone; EU-Staaten